1997
DOI: 10.1038/sj.bmt.1700985
|View full text |Cite
|
Sign up to set email alerts
|

Antithrombin-III for the treatment of chemotherapy-induced organ dysfunction following bone marrow transplantation

Abstract: Summary:with lethal organ dysfunction in the renal, pulmonary and cardiac systems. 5-8A hypercoaguable state has been demonstrated to occur A hypercoaguable state has been shown to follow highdose chemotherapy for bone marrow transplantation in many patients following bone marrow transplantation (BMT). 6,7,[9][10][11][12][13][14][15][16] Specifically, the natural anticoagulants (BMT). Deficiency of the natural anticoagulants, antithrombin III (AT-III), protein C and protein S cor-(antithrombin-III (AT-III), pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 0 publications
1
46
0
2
Order By: Relevance
“…[86][87][88] However, concordant with prior studies in adults, a recent large pediatric transplant trial in which 91 children received preemptive ATIII replacement (ATIII given when plasma ATIII activity p70%) demonstrated that ATIII administration did not reduce the incidence of VOD compared to the control group of 71 children who received no VOD prophylaxis. 89 Prostaglandin E1 (PGE1) is a vasodilator with a cytoprotective effect on endothelium as well as being an inhibitor of platelet aggregation with prothrombolytic activity.…”
Section: Antithrombin III and Prostaglandin E1supporting
confidence: 53%
“…[86][87][88] However, concordant with prior studies in adults, a recent large pediatric transplant trial in which 91 children received preemptive ATIII replacement (ATIII given when plasma ATIII activity p70%) demonstrated that ATIII administration did not reduce the incidence of VOD compared to the control group of 71 children who received no VOD prophylaxis. 89 Prostaglandin E1 (PGE1) is a vasodilator with a cytoprotective effect on endothelium as well as being an inhibitor of platelet aggregation with prothrombolytic activity.…”
Section: Antithrombin III and Prostaglandin E1supporting
confidence: 53%
“…As prophylaxis against hepatic VOD, UDCA, LMWH and PGE1 have been favorably reported (18)(19)(20), while conservative treatments of hepatic VOD include rt-PA, DF, AT-III and PGE1 (6,7,21). In this case, we tried all of the above -except for rt-PA -and all failed.…”
Section: Discussionmentioning
confidence: 92%
“…30,31 There is already evidence suggesting a role of this agent in transplant-related organ dysfunction. 32,33 Alternatively, or in addition, there may be a direct role of platelets in the development and progression of multiorgan dysfunction. It has been shown that consumption of platelets on the endothelial cell surface has adverse clinical consequences.…”
Section: Discussionmentioning
confidence: 99%